Legitimacy the state and beyond - Sevel, Michael; Sadurski, Wojciech 1950-; Walton, Kevin (Law teacher) (Oxford, United Kingdom New York Oxford University Press, 2019)
Traditionally, legitimacy has been associated exclusively with states. But are states actually legitimate? And in light of the legalization of international norms why should discussions of legitimacy focus only on the nation-state? The essays in this collection examine the nature of legitimacy, the legitimacy of the state, and the legitimacy of supranational institutions. The collection begins by asking: What sort of problem is legitimacy? Part I considers competing theories, in particular the work of John Rawls. Part II looks at the legitimacy of state apparatus, its institutions, officials, and the rule of law, and the future of state sovereignty. Part III expands the scope of legitimacy beyond the state to supranational institutions and international law. Written by theorists of considerable standing, the essays in this volume will be of interest to students and scholars of law, politics, and philosophy looking for ways of approaching the problem of how extra-territorial affairs affect a state's written and unwritten agreements with its citizens in a world where laws and norms with legal effect are increasingly made beyond the state.
Introduction, Wojciech Sadurski, Michael Sevel, and Kevin Walton; The Control Theory of Legitimacy, Philip Pettit; Legitimate Political Authority and Expertise, Fabienne Peter; Another Voluntarism: John Rawls on Political Legitimacy, Paul Weithman; The Future of State Sovereignty, Joseph Raz; The Legitimacy of Whom?, Nicole Roughan; The Rule of Law and State Legitimacy, Martin Krygier; The Nation State's Legitimation in Post-National Society: A Social Systems Perspective of Values in Legality and Power, Jifi Pfibdn; Conceptions of Public Reason in the Supranational Sphere and Legitimacy beyond Borders, Wojciech Sadurski; Who's Afraid of Suprastate Constitutional Theory? Two Reasons to be Sceptical of the Sceptics, Cormac Mac Amhlaigh; Perfectionist Liberalism and the Legitimacy of lnternational Law, Michael Sevel; Legitimacy Criticisms oflnternational Courts: Not Only Fuzzy Rhetoric?, Andreas Follesdal
Includes bibliographical references and index.
Keywords: Legitimacy of governments. -- Electronic books; Political science -- Philosophy